Non dentigerous variant of unicystic ameloblastoma: A case report - R Aravindhan; K T Magesh; P Suresh Kumar; T Elangovan; M Sathyakumar (Wolters Kluwer Medknow Publications, 2014)
Unicystic ameloblastoma is one of the placid jaw tumors comprising about 6-15% of ameloblastoma, it stands unexampled when it comes to the pathomorphological features. We discuss a case of unicystic ameloblastoma that is consonant with the nondentigerous multilocular unicystic ameloblastoma. The case was initially misdiagnosed as ameloblastic fibroma in a private diagnostic centre. Upon examining the resected specimen, we derived at the diagnosis of unicystic ameloblastoma, 1.2.3 type. The age of our case is also akin to the previous literature.